Analisis Potensi Wisata Berbasis Budaya dengan Pendekatan Community Based Tourism (CBT) di Desa Budaya Lung Anai, Kutai Kartanegara - Eman Sukmana; Himawan Brahmantyo; Tauhid Hira (EDUTOURISM Journal Of Tourism Research, 2019)
In 2005 Lung Anai Village was inaugurated by the Government of Kutai Kartanegara Regency as a cultural village based on the survey results and the cultural uniqueness of the Dayak Kenyah Tribe. Thus,on July 25, 2007 Lung Anai was established as a definitive village that stood alone by the Decree of the Kukar Regent No. 180,188 / HK-794/2007. The stipulation is expected to be able to boost economic development for the welfare of the community and increase the Kukar Regional Original Income (PAD) as well as to preserve the culture of Dayak Kenyah Lepoq Jalan tribes in Lung Anai Village. But in reality the goal has not been realized properly, until this year Lung Anai has not become a leading destination in Kukar. If observed in the literature, there is still a considerable gap with other cultural / tourist villages that have developed even independent in East Kalimantan. This study aims to comprehensively analyze the tourism potentials of Lung Abai village based on culture by conducting a community-based tourism (CBT) approach or community-based tourism. In addition, this research is also expected to be able to provide theoretical and technical recommendations for the Regional Government of Kutai Kartanegara District and stakeholders who have a common interest in developing the Lung Anai Cultural Village.